Single-component low-temperature curing epoxy glue for component bonding and preparation method of single-component low-temperature curing epoxy glue

By using a composite single-component low-temperature curing epoxy adhesive in component bonding, the coordinated cooperation of bisphenol F-type and bisphenol A-type epoxy resin, calcium sulfate whiskers and toughening modifiers, the problem of insufficient curing and toughness of epoxy adhesive at high temperatures is solved, and efficient low-temperature curing and tensile performance improvement is achieved.

CN119875557APending Publication Date: 2025-04-25东莞市博翔电子材料有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510095673.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the bonding operation of components, the curing of epoxy adhesive requires a higher temperature, resulting in poor high temperature resistance of components and cannot withstand long-term high-temperature baking. Moreover, the toughness of epoxy resin is poor, and it is prone to brittle breakage, which limits the application of epoxy adhesive in the electronic product field.

Method used

The single-component low-temperature curing epoxy glue is used to combine bisphenol F-type and bisphenol A-type epoxy resins, and calcium sulfate whiskers are preferred as additives, and toughening modifiers are added to coordinate the performance of the epoxy glue to improve its curing speed and tensile performance under low temperature conditions.

Benefits of technology

The epoxy adhesive that quickly cures under low temperature conditions is achieved, which improves its bonding effect and tensile performance in component bonding, avoids brittle breakage problems, and is suitable for use in the electronic product field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of epoxy adhesives, and particularly discloses a single-component low-temperature curing epoxy adhesive for component bonding and a preparation method of the single-component low-temperature curing epoxy adhesive. The epoxy resin and the curing agent are compounded respectively, the calcium sulfate whisker is preferably selected as an additive, the toughening modifier is further added for assistance, and the performance of the epoxy glue is optimized through synergistic cooperation of the components. The single-component low-temperature curing epoxy glue is very suitable for being applied to the bonding process of components, not only can overcome the contradiction between the bonding effect and the precision of the components, but also is not prone to failure in the using process, and fully overcomes the defects in related technologies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of epoxy adhesives, and more specifically, to a one-component low-temperature curing epoxy adhesive for bonding components and a preparation method thereof. Background Art

[0002] CCS (Cells Contact System, integrated busbar) is one of the core components of new energy battery packs. It is connected into a whole by hot pressing or riveting processes such as signal acquisition components (wiring harness / FPC / FFC, etc.), plastic structural parts, copper and aluminum busbars, etc., to achieve high-voltage series and parallel connection of battery cells, as well as temperature sampling and battery voltage sampling functions of the battery. It is part of the BMS system and can be used in new energy power batteries, energy storage batteries and other fields. With the continuous development of new energy vehicle power battery integration technology and the acceleration of applications in the energy storage field, driven by factors such as automation, cost reduction and efficiency improvement, the current CCS technology route presents a diversified development trend. Information acquisition solutions include wiring harness, PCB, FPC, FFC, FDC and other solutions. The integrated process also includes injection molding brackets, blister molding, hot pressing, die-cut PC, etc. At the same time, the industry is constantly innovating, and new solutions such as FCC sampling components, FPC / CCS de-SMT, and intelligent CCS are constantly being nurtured.

[0003] In the processing technology of CCS, dispensing is an important step. According to the different processing parts, it is divided into connector dispensing, nickel sheet dispensing, NTC dispensing and other operation forms. Commonly used adhesives for dispensing processing include acrylic adhesives, silicone adhesives, polyurethane adhesives, epoxy adhesives and other types. Acrylic adhesives are chemical reaction adhesives based on various types of acrylic esters. Acrylic adhesives are one of the most dynamic adhesive varieties today. With the continuous development of new technologies and the improvement of performance, their applications are more extensive. Silicone adhesives have unique heat resistance and low temperature resistance, good electrical properties and weather resistance, chemical stability, hydrophobic moisture resistance, oxidation resistance, air permeability and elasticity, etc. The electrical properties change very little in a wide temperature range, and the dielectric loss is low. Polyurethane (PU) adhesives have excellent performance, rapid development and wide application. PU polymers with different molecular structures can be designed and manufactured according to the requirements of different product occasions. It can be divided into: polyisocyanate polyurethane, two-component polyurethane, one-component polyurethane, modified polyurethane, reactive polyurethane. Epoxy resin refers to an oligomer that contains two or more epoxy groups in one molecule and can form a three-dimensional network structure in the presence of an appropriate curing agent. It is a thermosetting resin. Epoxy resin has excellent mechanical properties, electrical insulation properties, corrosion resistance and bonding properties.

[0004] With respect to the above-mentioned related technologies, the inventors believe that in the bonding operation of components, the curing of epoxy adhesives generally needs to be carried out at a relatively high temperature, while the high temperature resistance of components is generally poor and they cannot withstand long-term high-temperature baking. If the baking is carried out at a relatively low temperature, the bonding effect will be poor, while if the baking is carried out at a relatively high temperature, the precision of the components will be easily affected. Moreover, the toughness of epoxy resins is relatively poor, and brittle fracture is prone to occur during actual application. The above defects have caused great restrictions on the application of epoxy adhesives in the field of electronic products. Summary of the invention

[0005] In the related art, it is difficult to strike a balance between the bonding effect of epoxy adhesives and the precision of components, and epoxy resins have poor toughness and are prone to brittle fracture during actual application, which greatly limits the application of epoxy adhesives in the field of electronic products. In order to improve the above defects, the present application provides a single-component low-temperature curing epoxy adhesive for component bonding and a preparation method thereof.

[0006] In a first aspect, the present application provides a one-component low-temperature curing epoxy adhesive for bonding components, which adopts the following technical solution: A single-component low-temperature curing epoxy adhesive for bonding components comprises the following components in parts by weight: 28-32 parts of bisphenol F epoxy resin, 14-16 parts of bisphenol A epoxy resin, 6-8 parts of polyurethane modified epoxy resin, 2.2-2.8 parts of calcium sulfate whiskers, 6-14 parts of toughening modifier, 0.5-1.0 parts of stabilizer, 25-35 parts of curing agent, 7-9 parts of curing accelerator, 6-8 parts of thixotropic agent and 20-30 parts of filler; the curing agent comprises the following components in weight percentage: 8-15% of hexamer mercaptan curing agent, 28-32% of polyetheramine curing agent, and the balance is supplemented to 100% by diaminodiphenylmethane.

[0007] By adopting the above technical solution, the present application respectively compounded the epoxy resin and the curing agent, and preferably selected calcium sulfate whiskers as additives, and also added a toughening modifier for assistance, and optimized the performance of the epoxy adhesive through the synergistic coordination of the above components. Among the three epoxy resins selected in this application, the bisphenol F type epoxy resin has the highest content, which can effectively improve the elongation at break of the epoxy adhesive; the bisphenol A type epoxy resin has greater rigidity, which helps to improve the tensile properties of the epoxy adhesive; the polyurethane modified epoxy resin has good flexibility and adhesion, which can form a firm bond between the epoxy adhesive and the components. Among the curing agents, diaminodiphenylmethane has greater rigidity, and can effectively improve the overall tensile properties of epoxy adhesive through synergistic effects with bisphenol A epoxy resin; the chain structure of the polyetheramine curing agent has good compatibility with diaminodiphenylmethane, and has little inhibitory effect on diaminodiphenylmethane. Through synergistic cooperation with polyurethane epoxy resin, the epoxy adhesive can be given good flexibility, and internal stress can be dispersed, cracking can be reduced, and thus tensile properties can be improved; through the synergistic cooperation of the polyetheramine curing agent and diaminodiphenylmethane, the epoxy adhesive can be cured in a shorter time, and the hexamer thiol curing agent can further accelerate the curing speed on this basis, and reduce the temperature requirements of the curing reaction. The above-mentioned epoxy resin and curing agent can also produce synergistic effects with calcium sulfate whiskers and toughening modifiers, so that the epoxy adhesive has a higher tensile strength and is not prone to brittle fracture. It can be seen that the one-component low-temperature curing epoxy adhesive of the present application is very suitable for application in the bonding process of components. It not only overcomes the contradiction between the bonding effect and the precision of components, but also is not prone to failure during use, fully overcoming the defects in the relevant technology.

[0008] Preferably, the toughening modifier comprises fully vulcanized nano-carboxylated nitrile rubber.

[0009] By adopting the above technical solution, the fully vulcanized nano-carboxyl nitrile rubber has a toughening effect and can enhance the three-dimensional network structure of the epoxy adhesive, thereby improving the tensile strength of the epoxy adhesive.

[0010] Preferably, the average particle size of the fully vulcanized nano-carboxylated nitrile rubber is 60-120 nm.

[0011] By adopting the above technical solution, the present application optimizes the average particle size of the fully vulcanized nano-carboxyl nitrile rubber, fully enhances the three-dimensional network structure of the epoxy adhesive, and helps to improve the tensile strength of the epoxy adhesive.

[0012] Preferably, the toughening modifier also includes carboxyl-terminated liquid nitrile rubber.

[0013] By adopting the above technical scheme, the carboxyl-terminated liquid nitrile rubber has good compatibility with the fully vulcanized nano-carboxyl nitrile rubber and has good fluidity. It can synergistically enhance the three-dimensional network structure of the epoxy adhesive with the fully vulcanized nano-carboxyl nitrile rubber, and can also undergo microphase separation with the epoxy resin to form a sea-island structure that can absorb and consume energy, which helps to improve the elongation at break of the epoxy adhesive.

[0014] Preferably, the weight of the carboxyl-terminated liquid nitrile rubber accounts for 40-55% of the total weight of the toughening modifier.

[0015] By adopting the above technical solution, the present application optimizes the proportion of terminal carboxyl liquid nitrile rubber in the toughening modifier, which helps to improve the elongation at break of the epoxy adhesive.

[0016] Preferably, the toughening modifier further comprises carboxyl-terminated β-cyclodextrin.

[0017] By adopting the above technical solution, the carboxyl-terminated β-cyclodextrin can be used as a physical cross-linking point in the epoxy adhesive, and its cyclic structure and intramolecular hydrogen bonds give it higher rigidity, thereby effectively improving the elongation at break of the epoxy resin.

[0018] Preferably, the carboxyl-terminated β-cyclodextrin is prepared according to the following method: β-cyclodextrin is added to a sodium hydroxide solution, heated and stirred to obtain a cyclodextrin solution, and then a chloroacetic acid aqueous solution is added under heating conditions in a water bath to react. After the reaction is completed, hydrochloric acid is used to neutralize, and ethanol is added to precipitate after standing overnight, and then filtered, the filter cake is mixed with water, and ethanol is added again to precipitate, and the precipitate is dried to obtain terminal carboxyl-β-cyclodextrin.

[0019] By adopting the above technical scheme, the present application uses a reaction with cyclodextrin to replace the hydroxyl group in β-cyclodextrin with the carboxymethyl group in chloroacetic acid, and obtains terminal carboxyl-β-cyclodextrin after purification and extraction.

[0020] Preferably, the filler is a mixture of calcium carbonate and silica fume in a weight ratio of (3-5):1.

[0021] By adopting the above technical solution, the present application optimizes the composition and proportion of the filler and improves the elongation at break of the epoxy adhesive.

[0022] Preferably, the calcium sulfate whiskers are prepared according to the following method: Phosphogypsum and hydrochloric acid are mixed in a reaction container, and sodium oleate and sodium stearate are added. The mixture is heated in an oil bath and filtered while hot. The filter residue is washed with hot water and then vacuum dried to obtain calcium sulfate whiskers.

[0023] By adopting the above-mentioned technical scheme, the present application prepared calcium sulfate whiskers using phosphogypsum as raw material, and organically modified the calcium sulfate whiskers by sodium oleate and sodium stearate, thereby improving the dispersion effect of the calcium sulfate whiskers, enhancing the compatibility between the calcium sulfate whiskers and the epoxy resin, and helping to improve the tensile strength of the epoxy adhesive.

[0024] In a second aspect, the present application provides a method for preparing a one-component low-temperature curing epoxy adhesive for bonding components, using the following technical solution.

[0025] A method for preparing a one-component low-temperature curing epoxy adhesive for bonding components, comprising the following steps: (1) mixing bisphenol F epoxy resin, bisphenol A epoxy resin and polyurethane modified epoxy resin to obtain a composite epoxy resin for standby use; mixing a toughening modifier, a stabilizer, a curing accelerator and a thixotropic agent to obtain an auxiliary agent for standby use; mixing calcium sulfate whiskers and a filler to obtain a filling material for standby use; (2) The compounded epoxy resin, curing agent, auxiliary agent and filling material are mixed, and after stirring and vacuum degassing, the mixture is sealed and refrigerated to obtain a single-component low-temperature curing epoxy adhesive for bonding components.

[0026] By adopting the above technical solution, the present application first prepares the compound epoxy resin, curing agent, auxiliary agent and filling material separately, and then mixes these components to obtain a single-component low-temperature curing epoxy adhesive for component bonding.

[0027] In summary, this application has the following beneficial effects: 1. The present application compounded epoxy resin and curing agent respectively, and selected calcium sulfate whisker as an additive, and added a toughening modifier for assistance, and optimized the performance of epoxy adhesive through the synergistic coordination of the above components. The single-component low-temperature curing epoxy adhesive of the present application is very suitable for use in the bonding process of components, which not only overcomes the contradiction between the bonding effect and the precision of components, but also is not prone to failure during use, fully overcoming the defects in the relevant technology.

[0028] 2. In the present application, the fully vulcanized nano-carboxylated nitrile rubber and the carboxylated liquid nitrile rubber are preferably used as the components of the toughening modifier, which helps to improve the tensile properties of the epoxy adhesive and increases the tensile strength and elongation at break of the epoxy adhesive.

[0029] 3. The present application further selects terminal carboxyl-β-cyclodextrin as a component of the toughening modifier. Terminal carboxyl-β-cyclodextrin can serve as a physical crosslinking point in the epoxy adhesive, and its cyclic structure and intramolecular hydrogen bonds give it higher rigidity, thereby effectively improving the elongation at break of the epoxy resin. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0031] Preparation Example of Calcium Sulfate Whiskers The following is an explanation using Preparation Example 1.

[0032] Preparation Example 1 In this preparation example, calcium sulfate whiskers were prepared according to the following method: In a reaction container, 100 g of phosphogypsum and 1 L of 2 mol / L hydrochloric acid were mixed, and 2 g of sodium oleate and 6 g of sodium stearate were added. The mixture was heated in an oil bath at 140°C for 60 min and filtered while hot. The filter residue was washed with hot water at 85°C and then vacuum dried at 90°C for 24 h to obtain calcium sulfate whiskers.

[0033] Preparation Example of Carboxyl-Terminated β-Cyclodextrin The following is an explanation using Preparation Example 2.

[0034] Preparation Example 2 In this preparation example, In this preparation example, carboxyl-terminated β-cyclodextrin was prepared according to the following method: 0.05 mol of β-cyclodextrin was added to 1.5 L of 25 wt% sodium hydroxide solution, and the solution was stirred at 35°C for 0.5 h to obtain a cyclodextrin solution. A chloroacetic acid aqueous solution was then added under heating conditions at 65°C in a water bath to react for 5 h. After the reaction, 35 wt% hydrochloric acid was used to adjust the pH to 7. After standing overnight, ethanol was added for precipitation, and then filtered. After the filter cake was mixed with water, ethanol was added to the mixture again for precipitation. The precipitate was dried to obtain terminal carboxyl-β-cyclodextrin. Example

[0035] Examples 1-5 The following description is given by taking Example 1 as an example.

[0036] Example 1 In this embodiment, the bisphenol F epoxy resin is selected from American Hansen Epikote 862 bisphenol F epoxy resin, the bisphenol A epoxy resin is selected from YD-128 epoxy resin, and the polyurethane modified epoxy resin is selected from UMEP1002 epoxy resin; the calcium sulfate whiskers are prepared according to the method of Preparation Example 1, the toughening modifier is selected from fully vulcanized nano-carboxyl nitrile rubber (average particle size 150nm, acrylonitrile unit mass fraction is 26%), the stabilizer is selected from salicylic acid, the hexamer mercaptan curing agent is cross-linked by pentaerythritol tetramercaptopropionate and EP828 epoxy resin in a weight ratio of 3:1, the cross-linking temperature is 100°C, and the cross-linking time is 1h; the polyetheramine curing agent is selected from polyetheramine MA223; the curing accelerator is selected from Kawai MC120D, the thixotropic agent is selected from fumed silica R202, and the filler is selected from silica fume (average particle size 0.28μm).

[0037] The present embodiment provides a one-component low-temperature curing epoxy adhesive for component bonding, comprising the following components: 28kg of bisphenol F epoxy resin, 14kg of bisphenol A epoxy resin, 6kg of polyurethane modified epoxy resin, 2.2kg of calcium sulfate whiskers, 6kg of toughening modifier, 0.5kg of stabilizer, 25kg of curing agent, 7kg of curing accelerator, 6kg of thixotropic agent, and 20kg of filler; the curing agent comprises the following components in terms of weight percentage: 8% of hexamer mercaptan curing agent, 28% of polyetheramine curing agent, and the balance is supplemented to 100% by diaminodiphenylmethane.

[0038] This embodiment provides a method for preparing a one-component low-temperature curing epoxy adhesive for bonding components, comprising the following steps: (1) mixing bisphenol F epoxy resin, bisphenol A epoxy resin and polyurethane modified epoxy resin to obtain a composite epoxy resin for standby use; mixing a toughening modifier, a stabilizer, a curing accelerator and a thixotropic agent to obtain an auxiliary agent for standby use; mixing calcium sulfate whiskers and a filler to obtain a filling material for standby use; (2) The compounded epoxy resin, curing agent, auxiliary agent and filling material are mixed, and after stirring and vacuum degassing, the mixture is sealed and refrigerated at -20°C to obtain a single-component low-temperature curing epoxy adhesive for bonding components.

[0039] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of the epoxy adhesive.

[0040] Table 1 Raw material ratio of epoxy adhesive sample Example 1 Example 2 Example 3 Example 4 Example 5 Bisphenol F epoxy resin / kg 28 29 30 31 32 Bisphenol A epoxy resin / kg 14 14.5 15 15.5 16 Polyurethane modified epoxy resin / kg 6 6.5 7 7.5 8 Calcium sulfate whiskers / kg 2.2 2.3 2.5 2.7 2.8 Toughening modifier / kg 6 8 10 12 14 Stabilizer / kg 0.5 0.6 0.8 0.9 1.0 Curing agent / kg 25 28 30 32 35 Hexamer mercaptan curing agent ratio 8% 10% 11% 13% 15% Proportion of polyetheramine curing agent 28% 29% 30% 31% 32% Diaminodiphenylmethane 64% 61% 59% 56% 53% Curing accelerator / kg 7 7.5 8 8.5 9 Thixotropic agent / kg 6 6.5 7 7.5 8 Example 6 The difference between this embodiment and embodiment 5 is that the average particle size of the fully vulcanized nano-carboxylated nitrile rubber is 120 nm.

[0041] Example 7 The difference between this embodiment and embodiment 5 is that the average particle size of the fully vulcanized nano-carboxylated nitrile rubber is 90 nm.

[0042] Example 8 The difference between this embodiment and embodiment 5 is that the average particle size of the fully vulcanized nano-carboxylated nitrile rubber is 60 nm.

[0043] Example 9 The difference between this embodiment and embodiment 8 is that the toughening modifier further comprises carboxyl-terminated liquid nitrile rubber, and the weight of the carboxyl-terminated liquid nitrile rubber accounts for 30% of the total weight of the toughening modifier.

[0044] Example 10 The difference between this embodiment and embodiment 9 is that the weight of the carboxyl-terminated liquid nitrile rubber accounts for 40% of the total weight of the toughening modifier.

[0045] Embodiment 11 The difference between this embodiment and embodiment 9 is that the weight of the carboxyl-terminated liquid nitrile rubber accounts for 47% of the total weight of the toughening modifier.

[0046] Example 12 The difference between this embodiment and embodiment 9 is that the weight of the carboxyl-terminated liquid nitrile rubber accounts for 55% of the total weight of the toughening modifier.

[0047] Embodiment 13 The difference between this embodiment and embodiment 12 is that the toughening modifier also includes terminal carboxyl-β-cyclodextrin, which is prepared according to the method of preparation example 2, and the weight of terminal carboxyl-β-cyclodextrin accounts for 4.5% of the total weight of the toughening modifier.

[0048] Embodiment 14 The difference between this embodiment and embodiment 13 is that the filler is a mixture of calcium carbonate and silica fume in a weight ratio of 3:1, and the average particle size of the calcium carbonate is 1.4 μm.

[0049] Embodiment 15 The difference between this embodiment and embodiment 14 is that the filler is a mixture of calcium carbonate and silica fume in a weight ratio of 4:1.

[0050] Example 16 The difference between this embodiment and embodiment 14 is that the filler is a mixture of calcium carbonate and silica fume in a weight ratio of 5:1.

[0051] Comparative Example Comparative Example 1 In this comparative example, the epoxy resin is EP-828EL, the rubber particles are MX125 from KANEKA, the curing agent is 1 kg of salicylic acid and pentaerythritol tetrakis(3-mercaptopropionic acid), the curing accelerator is Kawai MC120D, and the thixotropic agent is fumed silica R202.

[0052] This comparative example provides a one-component low-temperature curing epoxy adhesive, comprising the following components: 40 kg of epoxy resin, 20 kg of rubber particles, 30 kg of curing agent, 1 kg of curing accelerator, 3 kg of thixotropic agent, 15 kg of silicon micropowder, and 10 kg of talcum powder.

[0053] Comparative Example 2 The difference between this comparative example and Example 1 is that the components of the epoxy adhesive do not include calcium sulfate whiskers.

[0054] Comparative Example 3 The difference between this comparative example and Example 1 is that the epoxy adhesive composition does not include a toughening modifier.

[0055] Comparative Example 4 The difference between this comparative example and Example 1 is that all bisphenol F epoxy resins are replaced by bisphenol A epoxy resins.

[0056] Comparative Example 5 The difference between this comparative example and Example 1 is that all polyurethane type epoxy resins are replaced by bisphenol A type epoxy resins.

[0057] Comparative Example 6 The difference between this comparative example and Example 1 is that the polyetheramine curing agent is completely replaced by diaminodiphenylmethane.

[0058] Comparative Example 7 The difference between this comparative example and Example 1 is that all the hexavalent mercaptan curing agents are replaced by diaminodiphenylmethane.

[0059] Performance testing methods 1. Rapid curing test The epoxy adhesive was subjected to a heat curing test at 60°C and the curing time was recorded. Then, based on the curing time of Comparative Example 1, the ratio between the curing time of each embodiment and the comparative example and the curing time of Comparative Example 1 was calculated. The ratio was recorded as the relative curing time. The results are shown in Table 2.

[0060] 2. Tensile properties Referring to GB / T 2567-2021 Test method for properties of resin castings, the tensile strength of the epoxy adhesive was tested, and then the tensile strength of Comparative Example 1 was used as a benchmark to calculate the ratio between the tensile strength of each embodiment and the comparative example and the tensile strength of Comparative Example 1. The ratio was recorded as the relative tensile strength. The results are shown in Table 2.

[0061] Referring to GB / T 2567-2021 Test method for properties of resin castings, the elongation at break of the epoxy adhesive was detected, and then the elongation at break of comparative example 1 was used as a benchmark to calculate the ratio between the elongation at break of each embodiment and comparative example and the elongation at break of comparative example 1, and the ratio was recorded as relative elongation. The results are shown in Table 2.

[0062] Table 2 Test results Combining Examples 1-16 and Comparative Examples 1-7 and Table 2, it can be seen that only the curing time of Comparative Examples 6 and 7 is longer than that of Comparative Example 1. This is because the present application achieves rapid curing through the synergistic combination of polyetheramine curing agent, diaminodiphenylmethane, and hexamercaptan curing agent, while Comparative Examples 6-7 lack polyetheramine curing agent and hexamercaptan curing agent, respectively, resulting in the inability to fully realize the synergistic effect, and thus the curing time is relatively long.

[0063] Combining Example 1 and Comparative Example 1 and Table 2, it can be seen that the relative elongation measured in Example 1 is significantly higher than that in Comparative Example 1. This is because Examples 1-5 contain more bisphenol F epoxy resin, which alleviates the rigidity of the epoxy resin itself, and the polyetheramine curing agent and the polyurethane epoxy resin synergistically give the epoxy glue good flexibility, thereby improving the elongation at break of the epoxy glue.

[0064] Combining Example 1 and Comparative Example 2 with Table 2, it can be seen that in the absence of calcium sulfate whiskers or toughening modifiers, the tensile strength and elongation at break of the epoxy adhesive are both low, indicating that the synergistic effect of calcium sulfate whiskers and toughening modifiers helps to improve the tensile properties of the epoxy adhesive.

[0065] Combining Example 1 and Comparative Examples 4-7 and Table 2, it can be seen that the relative elongation at break measured in Comparative Examples 4-7 is relatively low. This is because Comparative Examples 4-5 use a bisphenol A epoxy resin with greater rigidity to replace the other two epoxy resins, resulting in excessive rigidity of the epoxy glue, thereby affecting the elongation at break; Comparative Examples 6-7 use diaminodiphenylmethane with greater rigidity to replace the other two curing agents, which also results in excessive rigidity of the epoxy glue, thereby affecting the elongation at break.

[0066] Combining Example 5 and Examples 6-8 with Table 2, it can be seen that when the average particle size of the fully vulcanized nano-carboxylated nitrile rubber is 60-120 nm, the fully vulcanized nano-carboxylated nitrile rubber fully enhances the three-dimensional network structure of the epoxy adhesive, thereby contributing to improving the tensile strength of the epoxy adhesive.

[0067] It can be seen from the combination of Example 8, Example 9-12 and Table 2 that the elongation at break measured by Example 9-12 is higher than that of Example 8, because the carboxyl-terminated liquid nitrile rubber has good compatibility with the fully vulcanized nano-carboxyl nitrile rubber, and has good fluidity, can synergistically enhance the three-dimensional network structure of the epoxy adhesive with the fully vulcanized nano-carboxyl nitrile rubber, and can also be microphase separated with the epoxy resin to form a sea-island structure that can absorb and consume energy, thereby helping to improve the elongation at break of the epoxy adhesive. Wherein, when the weight of the carboxyl-terminated liquid nitrile rubber accounts for 40-55% of the total weight of the toughening modifier, the elongation at break of the epoxy adhesive is higher.

[0068] Combining Example 12, Example 13 and Table 2, it can be seen that the elongation at break of Example 13 is relatively high. This is because the terminal carboxyl-β-cyclodextrin can serve as a physical cross-linking point in the epoxy glue, and its cyclic structure and intramolecular hydrogen bonds give it higher rigidity, thereby effectively improving the elongation at break of the epoxy resin.

[0069] It can be seen from Example 13, Examples 14-16 and Table 2 that when the filler is mixed with calcium carbonate and silica fume in a weight ratio of (3-5):1, it is more helpful to improve the elongation at break of the epoxy adhesive than pure silica fume.

[0070] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A one-component low-temperature curing epoxy adhesive for bonding components, characterized in that: The invention comprises the following components in parts by weight: 28-32 parts of bisphenol F epoxy resin, 14-16 parts of bisphenol A epoxy resin, 6-8 parts of polyurethane modified epoxy resin, 2.2-2.8 parts of calcium sulfate whisker, 6-14 parts of toughening modifier, 0.5-1.0 parts of stabilizer, 25-35 parts of curing agent, 7-9 parts of curing accelerator, 6-8 parts of thixotropic agent and 20-30 parts of filler; the curing agent comprises the following components in weight percentage: 8-15% of hexamer mercaptan curing agent, 28-32% of polyetheramine curing agent, and the balance is supplemented to 100% by diaminodiphenylmethane.

2. The one-component low-temperature curing epoxy adhesive for component bonding according to claim 1, characterized in that: The toughening modifier comprises fully vulcanized nano carboxyl nitrile rubber.

3. The one-component low-temperature curing epoxy adhesive for component bonding according to claim 2, characterized in that: The average particle size of the fully vulcanized nano-carboxyl nitrile rubber is 60-120 nm.

4. The one-component low-temperature curing epoxy adhesive for component bonding according to claim 2, characterized in that: The toughening modifier also includes carboxyl-terminated liquid nitrile rubber.

5. The one-component low-temperature curing epoxy adhesive for component bonding according to claim 4, characterized in that: The weight of the carboxyl-terminated liquid nitrile rubber accounts for 40-55% of the total weight of the toughening modifier.

6. The one-component low-temperature curing epoxy adhesive for component bonding according to claim 4, characterized in that: The toughening modifier also includes a carboxyl-terminated β-cyclodextrin.

7. The one-component low-temperature curing epoxy adhesive for component bonding according to claim 6, characterized in that: The carboxyl-terminated β-cyclodextrin is prepared according to the following method: β-cyclodextrin is added to a sodium hydroxide solution, heated and stirred to obtain a cyclodextrin solution, and then a chloroacetic acid aqueous solution is added under heating conditions in a water bath to react. After the reaction is completed, hydrochloric acid is used to neutralize, and ethanol is added to precipitate after standing overnight, and then filtered, the filter cake is mixed with water, and ethanol is added again to precipitate, and the precipitate is dried to obtain terminal carboxyl-β-cyclodextrin.

8. The one-component low-temperature curing epoxy adhesive for component bonding according to claim 1, characterized in that: The filler is prepared by mixing calcium carbonate and silica fume in a weight ratio of (3-5):

1.

9. The one-component low-temperature curing epoxy adhesive for component bonding according to claim 1, characterized in that: The calcium sulfate whiskers are prepared as follows: Phosphogypsum and hydrochloric acid are mixed in a reaction container, and sodium oleate and sodium stearate are added. The mixture is heated in an oil bath and filtered while hot. The filter residue is washed with hot water and then vacuum dried to obtain calcium sulfate whiskers.

10. The method for preparing a one-component low-temperature curing epoxy adhesive for bonding components according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Mixing bisphenol F epoxy resin, bisphenol A epoxy resin and polyurethane modified epoxy resin to obtain a compound epoxy resin, which is set aside; mixing a toughening modifier, a stabilizer, a curing accelerator and a thixotropic agent to obtain an auxiliary agent, which is set aside; mixing calcium sulfate whiskers and fillers to obtain a filling material, which is set aside; (2) The compounded epoxy resin, curing agent, auxiliary agent and filling material are mixed, and after stirring and vacuum degassing, they are sealed and refrigerated to obtain a single-component low-temperature curing epoxy adhesive for bonding components.

Citation Information

Cited By

  • Integrated busbar and processing method thereof

    CN121123576A

  • Laminated busbar

    CN224502251U